The inhibitory effect of rooibos on cytochromes P450 and downstream in vitro modulation of steroid hormones - Mugari, Mufaro Buhlebenkosi (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc)--Stellenbosch University, 2015.